Peran Kepala Sekolah sebagai Pemimpin Instruksional dalam Meningkatkan Kualitas Pembelajaran di Sekolah SMA Negeri 1 Kutacane - Purba, Sonia Gandi; Nopitasari, Pera; Nika, Ayu; Fhutu Neva, Rinda Annisa; Zega, Tasya Wiyandini (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to analyze the role of the principal as an instructional leader in improving the quality of learning at SMA Negeri 1 Kutacane. This study employs a qualitative approach with a descriptive research design. The subject of this study is the school principal, selected using purposive sampling. Data were collected through in-depth interviews and supported by documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that the principal has performed his role as an instructional leader quite optimally through academic supervision, teacher development, and the implementation of innovative learning programs. The principal also encourages the use of active learning models such as Problem Based Learning and the integration of technology in the learning process. In addition, efforts to improve learning quality are carried out through teacher training programs, learning evaluation, and continuous feedback. However, there are still challenges such as differences in students' abilities and teachers' readiness to implement innovative learning. In conclusion, the role of the principal as an instructional leader has a significant impact on improving the quality of learning. Therefore, strengthening teacher professional development and optimizing the use of learning evaluation results are highly recommended.